Example-Based Fluid Simulation - Chang, Ming (Université d'Ottawa / University of Ottawa, 2011)
We present a novel method for example-based simulation of fluid flow. We reconstruct fluid animation from physically based fluid simulation examples. Our framework shows how to decompose a given series of fluid motion example data into small units and then recompose them. We capture the properties of local fluid behavior by dicing the fluid motion example data into sequences of fragments, which have smaller volume and shorter length. We build a database out of these fragments, and propose a matching strategy to generate new fluid animation. To achieve highly efficient database query, we project our fragments onto lower dimensional subspace using Principal Component Analysis (PCA) approach, and construct our data structure as a kd-tree by treating each fragment as a point in this subspace. Our method has been implemented in synthesizing both two-dimensional (2D) and three-dimensional (3D) fluid’s velocity fields.